Strengthening KDEKS Governance for the Development of Muslim-Friendly Tourism in Indonesia - Ro'fah Setyowati; Kholifatul Muna; Muhammad Thoriq Adli (UPT Publikasi Ilmiah UNISBA, 2026)
The Regional Sharia Economic and Financial Committee (KDEKS) is a strategic institution at the regional level that plays a role in accelerating the development of the sharia economic and financial ecosystem, including Muslim-friendly tourism. However, as a relatively new institution, KDEKS still faces challenges such as weak cross-sectoral coordination, limited institutional capacity, suboptimal regulatory and budgetary support, and a lack of integrated policies for the development of Muslim-friendly tourism. This study aims to analyze the existence of KDEKS in the development of Muslim-friendly tourism in Indonesia and to formulate a governance strengthening model based on maqashid sharia. The study utilizes an empirical juridical method with statutory, conceptual, and theory-based approaches. Data were obtained through in-depth interviews with three informants from the National Sharia Economic and Financial Committee (KNEKS), the Ministry of Tourism, and the Halal Product Assurance Agency (BPJPH), as well as a literature review. Data analysis was carried out qualitatively through thematic grouping and legal interpretation using grammatical, systematic, and teleological methods. The results show that KDEKS plays a strategic role in strengthening inter-agency synergy, policy coordination, and the development of the halal ecosystem, although it still faces institutional and regulatory obstacles. This study offers a KDEKS governance strengthening model that integrates institutional governance, collaborative governance, and maqashid sharia, and recommends strengthening regulation, institutions, and cross-sectoral coordination to achieve integrated and sustainable Muslim-friendly tourism development.